Gravitational resedimentation as a fundamental process in filling fjords: Lessons from outcrops from a late Palaeozoic fjord in Namibia - Menozzo da Rosa, Eduardo; Isbell, John L.; McNall, Natalie; Fedorchuk, Nicholas; Swart, Roger (Sedimentology, 2023)
The stratigraphic architecture of fjords is complicated due to the delicate interplay between ice dynamics, sediment supply, relative sea-level fluctuations and slope failures. Glaciogenic sediment is prone to failure and to be carried downslope to the fjord floor through the entire spectrum of mass movements and subaqueous density flows, as the unstable paraglacial submarine landscape moves towards stability. Palaeofjords formed by Gondwanan glaciers during the late Palaeozoic Ice Age contain a compelling record of gravitational resedimentation in fjord depositional systems. This paper showcases the geomorphology and depositional history of a glacial cycle in the Orutanda fjord in north-western Namibia as an example of an overdeepened fjord basin fill dominated by products of subaqueous gravitational processes. During glaciation, the Orutanda glacier carved a 20 km long by 3.7 km wide glacial trough that embodies an overdeepened basin. Ice thickness during terminal glacial occupation of the fjord is estimated to had been up to 200 m based on the fjord geomorphology. The progressive retreat of the tidewater glacier, concomitant with marine flooding, increased accommodation space in the overdeepened basin during deglaciation. During this stage, proglacial sedimentation through iceberg rafting and settling of turbid plumes was outpaced by intense paraglacial downslope resedimentation of glacially-transported debris. Successive failures from the fjord walls and downslope resedimentation resulted in coalescing debrite–turbidite lobes on the fjord floor. Slide deposits, composed entirely of deformed debrites and turbidites, indicate that these resedimented facies were prone to renewed mass wasting. As the Orutanda glacier melted, the fjord experienced the axial progradation of a fjord-head delta registered only by turbidites and slide deposits derived from its collapse. The Orutanda fjord sheds light on the relevance of paraglacial mass wasting in overprinting glaciogenic deposits. This insight is key to understanding the role of glaciers versus non-glacial processes in producing the glacial deep-time record.
Keywords: Debris flows; Dwyka Group; dept.esc; late Palaeozoic Ice Age; mass wasting; paraglacial processes; peer-reviewed; turbidites

Reappraisal of Exceptionally Preserved S-Forms, Striae, and Fractures from Late Paleozoic Subglacial Surfaces in Paleofjords, NW Namibia - Fedorchuk, Nicholas D.; Isbell, John L.; Rosa, Eduardo L. M.; Swart, Roger; McNall, Natalie B. (Sedimentary Geology, 2023)
Determining the grounded ice dynamics of deep-time glaciations is limited by the scarcity of well-preserved subglacial erosional features and their irregular distribution. In particular, small-scale erosional features known as s-forms that are subglacially sculpted in bedrock by water and/or ice are rarely preserved from the pre-Cenozoic record. A detailed re-examination of two late Paleozoic (late Carboniferous–early Permian) glacially-polished, surfaces at the base of the Dwyka Gp. within paleofjords located in the Kaokoveld region of northwest Namibia reveals a range of erosional features including: complex, multi-directional striae that crosscut each other, crescentic markings, chattermark trails, sinuous furrows, linear furrows, transverse troughs, comma forms, sichelwannen, muschelbrüche, cavettos, a pothole, and rock drumlins. The first study location in the Sanitatis paleovalley is previously undescribed and consists of striae and fractures on a polished granite bedrock surface located on the paleovalley floor. Striae, crescentic markings, and chattermark trails indicate ice movement to the west/northwest (striae mean azimuth of 276°). The second location in the Hoarusib paleovalley was previously described and is located on a multi-level, resistant, quartzite bedrock ridge close to or on the valley wall. This location contains numerous s-forms, striae, and fractures, as well as onlapping glaciogenic sediments, including diamictite plastered within a pothole. Some of these features are superimposed on rock drumlins. These erosional features were likely formed by a combination of pressurized subglacial meltwater and glacial abrasion underneath a glacier as it flowed over and around a resistant bedrock outcrop. Orientations of striae and chattermark trails at the second location indicate a primary direction of ice movement toward the west/northwest (striae modal azimuth of 275°), a minor secondary movement to the southwest (255°), and abundant third-order striae indicating ice flow around bedrock obstacles. However, cross-cutting relations suggest the primary and secondary striae orientations are not related to two distinct glacial advances as previously thought. The complex relationships between striae, fractures, and s-forms suggest that a combination of pressure melting, abundant subglacial meltwater, debris-rich basal ice, and variable ice flow paths around resistant obstacles was required to form these features. We conclude that the study locations were overridden by relatively thick (>210 m) warm-based or polythermal glaciers that were confined to a network of fjords as ice receded and stagnated. The glaciers flowed west into present-day Brazil during the late Paleozoic and likely overtopped the paleovalley walls during times of ice maxima.
Keywords: Carboniferous; Dwyka; Erosional; Fjords; Glacial; Permian; dept.esc; peer-reviewed

Evaluation of physical and chemical proxies used to interpret past glaciations with a focus on the late Paleozoic Ice Age - Isbell, John L.; Vesely, Fernando Farias; Rosa, Eduardo L.M.; Pauls, Kathryn N.; Fedorchuk, Nicholas D.; Ives, Libby R.W.; McNall, Natalie B.; Litwin, Scott A.; Borucki, Mark K.; Malone, John E.; Kusick, Allison R. (Earth-Science Reviews, 2021)
The late Paleozoic Ice Age (LPIA) was one of Earth's most important Phanerozoic climatic events lasting for over 100 Mys. Despite its importance, its history is controversial with two hypotheses that portray glaciation differently (Fig. 1). Traditional views characterize the LPIA as a continuous glacial event that lasted from the Middle Mississippian until the Late Permian with a massive ice sheet that covered Gondwana throughout this interval. This approach often uses only one or two proxies to define the glaciation. The other emerging hypothesis suggests that numerous ice sheets occurred in Gondwana with individual glacial events lasting up to 10 Mys alternating with glacial minima/non-glacial intervals of similar duration. Both views are still prevalent. Both near- and far-field proxies are used to define the ice age. Near-field proxies include the occurrence/absence of diamictites, glaciotectonic deposits/landforms, striated clasts and clast pavements, outsized clasts (dropstones), rhythmites, cyclic diamictite-bearing successions, glendonites, grooved and striated surfaces, streamline landforms, and U-shaped paleovalleys. Detrital zircons and chemical index of alteration (CIA) studies help to delineate the occurrence, extent, and location of glaciation. Multiple complexities occur with the use of these proxies as different non-glacial processes and driving factors can produce similar features or results. Far-field proxies focus on identifying changes in eustacy. These include the occurrence of cyclic successions composed of alternating nonmarine and marine strata (cyclothems), depth of incised valleys, paleotopographic relief, phosphatic black shales, and changing oxygen isotope ratios. Like the near-field record, far-field proxies are complex indicators with varied nuances that make their application challenging. Here we discuss the limitations and use of these proxies and promote a multiproxy approach to investigating Earth's glacial intervals. We suggest that studies incorporate multiple proxies coupled with detailed environmental, paleoflow, and paleogeographic analyses to better constrain the occurrence, timing, and extent of glaciation and its influence on global systems. This approach will provide a robust view of the LPIA. We also consider the magnitude and nature of sea-level response to changing ice volumes by discussing ice-volume fluctuations, basin subsidence's modification of glacioeustacy, and sea-level's response to global isostatic adjustment (GIA). In considering these features, it becomes apparent that glacioeustacy is more complex than previously envisioned. © 2021 Elsevier B.V.
Keywords: Gondwana; Mississippian; Paleozoic; Pleistocene; dept.esc; glaciation; glacioeustacy; ice sheet; peer-reviewed